Molecular characterization and expression pattern of tobacco (Nicotiana tabacum) ascorbate oxidase gene - Zhihua Li; Jian Chen; Chao Wang; Yunjie Huang; Jiajun Wang; Shifei Dong; Lu Tang; Jiani Liu; Zebin Chen; Dingkang Wang; Shengguang Xu; Lei Yu (Biotechnology & Biotechnological Equipment, 2016)
The complete coding sequence of one tobacco (Nicotiana tabacum) gene, ascorbate oxidase (AO), was isolated by the application of reverse transcription-polymerase chain reaction. The tobacco AO gene consists of a 1722-bp open reading frame and encodes a protein of 573 amino acids. Sequence comparison analysis revealed that the tobacco AO protein shares high homology with the AO proteins of Lycopersicon esculentum (89%), Populus trichocarpa (75%), soybean (74%), castor bean (73%) and peach (73%). The prediction of transmembrane helices showed that tobacco AO might be a transmembrane protein. The expression profile was studied and the results indicated that the tobacco AO gene was diversely expressed in different tobacco tissues, including leaves, stem, roots and flowers. Our experiment laid the grounds for further research on this tobacco gene.